Evaluation of frequency of positive exercise-induced bronchospasm between swimmers and sedentary individuals - Laricy Martins da Mata; Regiane Coissi Sanches; Marceli Rocha Leite; Francis Lopes Pacagnelli; Luiz Carlos Marques Vanderlei; Flávio Danilo Mungo Pissulin
Abstract Introduction: Despite the prevalence of prescribed asthma, there is uncertainty about the incidence of exercise-induced bronchospasm (EIB). Objective: Compare the frequency of EIB between swimmers and sedentary individuals, and observe heart rate variability during bronchial activity. Methods: In total, 18 swimmers (group 1) and 18 sedentary individuals (group 2) were included. The participants rested for 30 minutes for evaluation of HRV. Blood pressure (PA), respiratory rate (RR), and pulse oxygen saturation (SpO2) were measured. The volunteers remained seated for the spirometry test (maneuver of forced vital capacity - FVC). This was repeated 5, 10, 15, 20, and 30 minutes after the exercise test. The statistical analysis used the Student t, Mann Whitney, and Shapiro-Wilks tests. The significance level was p <0.05. Results: The spirometry findings showed 3 sedentary individuals and 10 swimmers with obstructive ventilatory disorder (OVD). Only 2 of the sedentary and none of the swimmer group demonstrated positive bronchial provocation. A key criterion for diagnosing OVD, the relationship between forced expiratory volume in one second and FVC (FEV1/FVC), was statistically lower in the swimmer group. The measures of the root mean square of the successive differences between adjacent normal RR intervals, in a time interval (RMSSD), and the standard deviation of all normal RR intervals recorded in a time interval (SDNN) were significantly higher among the athletes. Conclusion: The bronchial provocation test identified a higher prevalence of bronchospasm among sedentary individuals. However, there was a reduction in the FEV1/FVC ratio and higher HRV in the group of swimmers.